Characteristics of autism spectrum disorder and susceptibility to radicalisation among young people: a qualitative study - Walter, Florian (The journal of forensic psychiatry & psychology, 2021)
Previous studies suggest an overrepresentation of autistic people among terrorist offenders, specifically lone-actors, as compared to the general population. At present, there is little literature which examines core autistic traits and how these may make individuals susceptible to adopting radical ideology. Such findings would support the identification of individuals who may require intervention, and help to minimise the risk of exploitation and criminalisation of individuals with autism. This study was commissioned by a specialist school for autistic children in England to provide guidance for staff on how to identify and manage autistic young people at risk of being radicalised. The study included 34 qualitative interviews with experts in the field. Participants included National Health Service staff, academics, educational staff and counter-terrorism officers, as well as young people with autism from the UK. This paper presents findings relating to the existing evidence; key autistic traits and environmental contexts that may contribute towards a susceptibility to radicalisation; the current safeguarding measures and referral system, and; appropriate interventions across the trajectory into radicalisation, specifically the role of early intervention. Findings will help support clinicians and criminal justice professionals when working with individuals who present with radical ideology and have an autism diagnosis.